The Effect of Extra-curricular Activities on the Development of Saudi Secondary-School EFL Students' Oral Performance in Al-Namas Province as perceived by EFL Teachers - Al-Omri, Khalid Ahmad Hindi; Ahmed, Mamdouh Ali (Journal of Educational and Psychological Sciences, 2019)
The study purpose was to determine the impact of extra-curricular activities on the improvement of EFL students' oral performance in Saudi secondary-schools, Al-Namas Province as perceived by EFL Teachers. In addition, identify the significant relationship at level (α ≤ 0.05) between the effect of extra-curricular activities adapted in Saudi secondary schools, and the oral performance of the students by the EFL teachers perspective. The study depended on a qualitative approach. The study population was EFL teachers working at secondary-school in Al-Namas Province, Saudi Arabia, and the researcher selected a random sample with size (50) of EFL teachers from secondary-schools. Research results was as follow:  there is a positive correlation between the effect of extra-curricular activities adapted in Saudi secondary schools, and the oral performance of the students from the perspective of EFL teachers; there is no statistically significant differences in the correspondent of the sample at level (α = 0.05) in the effect of extra-curricular activities on the development of Saudi secondary-school ELF students' oral performance due to Qualification; Extra-curricular activities help students increase their vocabulary. the study provided many recommendations: school management must organize programme's for extra-curricular activities inside school; school management be supposed to use high academic performance condition for allowing students to participate in extra-curricular activities; and students should be free to decide which curricular activities to participate in.
Keywords: extra-curricular activities; English language; secondary stage; education